Lithology Units Padaherang Area and Surrounding, Ciamis District, West Java Province - Gani, Reza Mohammad Ganjar; Firmansyah, Yusi (Journal of Geological Sciences and Applied Geology, 2021)
Administratively, Padaherang region and surrounding is included to kecamatan Padaherang, Ciamis Regency, West Java. The reason why this area is a research area is partly because the author feels that the area in Ciamis Regency is a southern mountainous area that is influenced by volcanism and sedimentation processes and other geological processes. In addition, there are still many geological problems that have not been fully revealed, so the author feels the need to conduct further and more detailed research. Objects to be studied in the field include rocks (description, sampling, direction of moves and slopes), indications of geological structures, and landscape appearances accompanied by sketch photos and additional data deemed to support the research results, The research steps carried out included several stages of work, namely the preparation stage, field work, laboratory research, and the stage of preparing reports. The trajectory that is traced in the field research that has been determined at the preparatory stage. If the trajectory is deemed inadequate, a search for additional trajectories is carried out. There are three methods used in geological mapping, namely the field orientation method, the compass trajectory method, the measuring tape method and the compass. In this mapping, the methods used are the field orientation method and the measuring tape and compass method. Threre are  five lithology units which is arrange at research area, these units of lithologi from the older to the younger is breccias unit, sandstone units,  claystone. Geology activity at research area predicted begun at Oligocen till Holocen era. first in Oligocen the volcanic activity is strong enough where the eruption produced the breccia and sandstone unit, this process stop at lower Miosen. And at the middle Miosen there is the tectonic activity hapenned. Limestone unit was diendapkan at middle Miocen, and claystone unit at upper Miocen, and quartery deposit is the younger unit at research area